الصناعة التعدينية وأثرها على التنمية الاقتصادية في ظل المستجدات البيئية في العالم - مداني, جميلة (جامعة الوادي - University of Eloued, 2019)
الصناعة التعدينية وأثرها على التنمية الاقتصادية في ظل المستجدات البيئية في العالم ملخص: يعتبر التوفيق بين الصناعة التعدينية والتنمية المستدامة تحديا لجميع العناصر الفاعلة في النشاط الاقتصادي والسياسي، من خلال تحديد السياسات والقوانين التي ترقي الصناعات التعدينية في ظل شروط الاستدامة، حيث يهتم العالم بتطوير الآليات لتحقيق مصالحة بين الصناعة التعدينية والتنمية المستدامة تسمح، من خلال حصر المشاكل البيئية الناتجة من هذه الصناعات التي تعتمد على الموارد الملوثة، بحيث تؤثر على استمرارية الإنتاج، الامر الذي جعل البحث عن موارد جديدة واستغلالها بكيفية اقتصادية للتلبية المستمرة والدائمة للأفراد حاليا ومستقبلا. بالرغم من الفوائد الاقتصادية لصناعة التعدين، إلا ان ترتب آثار من المواقع المتدهورة والحوادث الصناعية في جميع أنحاء العالم، أنتج اهتمام لتعبئة مختلف الجهات المعنية في دول العالم الصناعية من أجل صناعة تعدينية مستدامة؛ حيث أخذت هذه التعبئة في شكل الاتفاقيات والعهود والبروتوكولات الدولية، ووضعت شروط ومبادئ وقواعد توجيهية للإدارة السلوك للشركات الصناعية التعدينية. نتطرق في هذا البحث إلى أهمية الصناعة التعدينية في التنمية الاقتصادية، وكيفية مواكبتها مع متطلبات التنمية المستدامة في ظل التحديات الدولية الراهنة؛ مع اخذ بعض النماذج في العالم حول الصناعة التعدينية Mining industry and their impact on economic development in environmental changes in the world Abstract: Reconciliation is considered Between the mining industry Sustainable development is a challenge for all Actors in economic and political activity, Through the identification of policies and laws Which promotes mining industries Under conditions of sustainability, Where the world is concerned with developing mechanisms To achieve reconciliation between the mining industry Sustainable development allows, By limiting the environmental problems resulting from these industries Which depend on polluting resources, so as to affect the continuity of production. Which made the search for new resources and exploitation in an economic way to meet the ongoing and permanent for individuals now and in the future. Despite the economic benefits of the mining industry, the impact of degraded sites and industrial accidents around the world has generated interest in mobilizing the various stakeholders in the industrialized world for a sustainable mineralization industry. This mobilization took the form of international conventions, covenants and protocols, Principles and guidelines for the conduct management of industrial mining companies. In this research, we discuss the importance of the mineral industry in economic development and how to cope with the requirements of sustainable development in light of the current international challenges. Taking some models in the world around the mining industry,
Mining industry and their impact on economic development in environmental changes in the world
مقال